Cerebral infarction caused by a heart-breaking needle: a case report. (December 2016) - Ye, Shaodong; Li, Lin; Dong, Qiuting; Wang, Guogan
Abstract Background In this report, we describe a case of cerebral infarction caused by cardiac foreign body–induced infective endocarditis. We discuss the paradox of the treatment we used and highlight the need for careful examination of patients without histories and complaints of cardiac disease. Case presentation Our patient was a 48-year-old Asian woman who presented with symptoms of cerebral infarction without any characteristic features of infective endocarditis. Appropriate treatment had been delayed, which made her therapy a little bit complicated. The optimal treatment of our patient was apparently surgery. However, the appropriate timing of her operation is still argued among surgeons at our department because of her acute cerebral infarction. Conclusions Patients with cardiac foreign bodies need timely surgery, especially patients who display symptoms of nervous system or cardiovascular system imbalance. In this case report, we share our experiences with treating such a patient, which may have some clinical implications in a contradictory situation. To the best of our knowledge, this report is the first of its kind and will broaden understanding of the clinical diagnosis of this type of case.